Morphometric Nerve Fiber Analysis of the Human Inferior Alveolar Nerve: Lateral Asymmetry - MORIYAMA, Hiroshi; MIYAUCHI, Yasushi; GOTO, Noboru; EZURE, Hiromitsu; GOTO, Jun (Okajimas Folia Anatomica Japonica, 2002)
We studied morphometric nerve fiber analysis and the lateral asymmetry of the inferior alveolar nerve (IAN). Human IANs were resected at the mandibular foramen. The preparation of sections involved fixation, washing, dehydration, embedding, sectioning and staining as described in our previous reports. We estimated the average total number of myelinated axons in the right IAN to be 22,808, with an average transverse area of 37.6 μm2, an average perimeter of 23.0 μm, and average circularity ratio of 0.85, with the same measurements in the left IAN being 24,289, 33.9 μm2, 21.6 μm, and 0.86, respectively. Morphological differences between the right and left side were analyzed by applying parametric tests (unpaired t-test) to all measured items. According to these results, the IAN did not demonstrate notable lateral asymmetry in any measured item. We considered that these results were caused by using subjects with the same dentulous condition in both sides.